Theory of Everything: The Missing Link in Modern Physics, Which Solves all the Problems - Tannous, Edward (European Journal of Applied Sciences, 2024)
A theory with a simple physical model gives logical and reasonable answers to all the strange phenomena and difficult-to-understand problems in modern physics, from the theory of relativity, quantum mechanics QM, and up to the field of cosmology. It is a theory suitable for explaining phenomena from small particles to large bodies such as stars, galaxies, and the entire universe. In this article, we will define in an innovative manner how space-time is seen and we will give a different graphical representation to the special theory of relativity. We will show how the Lorentz transformation equations and the space-time interval are obtained from it, how light behaves in space-time, and according to it, how to obtain relativistic Doppler formulas. The most important thing in this article is that just as two bodies can be in two different times, according to the theory of relativity, they can also be simultaneously in two different locations. According to it, Heisenberg's uncertainty principle and quantum superposition can be explained. We will present for the first time a very common physical phenomenon, but unknown up to this day, which we will call "leap set". According to it, we will logically and deterministically explain the double-slit experiment of electrons and we will show that the result of the experiment is not a wave interference because the electron does not pass through the slits, but it performs a leap set to possible locations on the screen. Also, according to the same model, we will see the conditions and reasons for quantum entanglement and how it is obtained. We will also show the expansion of the universe and Hubble's law according to this theory and model, the Casimir effect as a cosmological phenomenon. We will discuss the possibility of the existence of a mirror world completely identical to our world, located at a distance of 2x13.8Gly in the space-time and we will prove that the material mass energy of the universe is zero.